The Effect of Perceived ROI on Perceived Value and Adoption Intention - Paransa, Rizki Pratama Johanis; Kusuma, Rr. Chusnu Syarifa Diah; Nugroho, Fajar Wahyu; Wulandari, Kurnia (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the role of perceived return on investment (ROI) in shaping perceived value and its impact on adoption intention toward digital branding among small and medium-sized enterprises (SMEs). A quantitative approach with an explanatory research design was employed, involving 100 SME owners in the Special Region of Yogyakarta, Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived ROI has a positive and significant effect on perceived value with a t-statistic of 4.562 and a p-value of 0.000 (
Keywords: Perceived ROI; Perceived Value; Adoption Intention; Digital Branding; SMEs